تطبيق ويغراوند (Wayground) في التقويم للتحصيل الدراسي في اللغة العربية في المرحلة المتوسطة - Mulyadi Mulyadi; Nabila Sakha Khairunnisa (Qawa’id: Jurnal Bahasa dan Sastra Arab, 2026)
This study aims to explore the pedagogical function and practical application of the Wayground (formerly known as Quizizz) application in measuring and evaluating Arabic language achievement within the junior high school context. The methodology used is based on a systematic analytical literature review of various relevant sources, including indexed scientific articles, books, and academic papers. Data were analyzed qualitatively using content analysis methods to identify the main educational advantages and technical limitations of this digital tool, as well as the appropriate ways to implement it effectively. The results indicate that Wayground holds great potential as an interactive, engaging, and objective assessment medium. It can significantly enhance students’ learning motivation, eliminate psychological pressure during tests, and reinforce vocabulary retention (mufradat). However, technical limitations such as internet dependency and its constraints in measuring productive skills need to be carefully considered. This research provides a comprehensive overview of Wayground in language evaluation, offering 4 pedagogical operational phases for teachers, and provides valuable recommendations for future blended assessment development in this field.